Assessing the effectiveness of payments for ecosystem services for diversifying rubber in Yunnan, China. (July 2015) - Smajgl, Alex; Xu, Jianchu; Egan, Stephen; Yi, Zhuang-Fang; Ward, John; Su, Yufang
Abstract: Monoculture rubber plantations are rapidly expanding throughout Southeast Asia. The Prefecture of Xishuangbanna is characterised as both an epicenter of Chinese biodiversity and rubber production. The rapid conversion of native primary forest into rubber plantations has introduced tensions between the competing political goals to conserve biodiversity and heritage landscapes – both driving the rapidly emerging tourism industry – and economic aspirations at household and district levels. In China, decision makers discuss payments for ecosystem service schemes to resolve these tensions. As a component of the policy development process, this research project was invited to inform the political debate. Agent-based simulations revealed perverse outcomes of payments for ecosystem services, intended to encourage the conversion of monoculture rubber into agroforestry rubber. As an outcome of this modelling-based initiative, managing agencies have revised previously drafted payment schemes and reconsidered the importance of monitoring and regulatory approaches. Highlights: We assess the effectiveness of payment for ecosystem services (PES) in the context of biodiversity and land use change. Our study shows that the current PES design in China can lead to perverse outcomes and a further increase of rubber. This result emerged from agent-based simulations and was then validated by stakeholders in a participatory research process. This work shifted the debate to effective monitoring and enforcement mechanisms as a prerequisite for institutional change.